Vitamin D Provision in Children with Congenital Epidermolysis Bullosa: Cross-Sectional Study - Irina Yu. Pronina; Nikolay N. Murashkin; Svetlana G. Makarova; Elena L. Semikina; Dmitry S. Yasakov; Stepan G. Grigoriev (Вопросы современной педиатрии, 2021)
Background. Children with congenital epidermolysis bullosa (CEB) can have vitamin D deficiency due to its malabsorption in intestine and reduced synthesis in skin as these patients have restrictions on staying in the sun. However, the prevalence of vitamin D insufficiency/deficiency among patients with CEB remains not fully studied due to the small samples' sizes in previously studies. Objective. Our aim was to study vitamin D provision in children with CEB. Methods. The study included children aged from 3 to 18 years old with simplex and dystrophic types of CEB hospitalized in our department. The serum level of 25(OH)D was determined via chemiluminescence immunoassay. Vitamin D deficiency was established at 25(OH)D concentration of 20-30 ng/ml, deficiency — < 10-20 ng/ml, deep deficiency — < 10 ng/ml. Results. The study included 129 children with CEB (62 (48%) males, median age 6 (3; 10) years). 101 patients had dystrophic type of disease, 28 — simplex. The median 25(OH)D serum concentration in children with CEB was 21.7 (13.0; 36.6) ng/ml. Vitamin D insufficiency was revealed in 36 (28%) patients, deficiency — in 38 (29%), deep deficiency — in 16 (12%). Independent predictors of 25(OH)D concentration were the type of CEB (concentration was higher in children with simplex type) and age (negative association), but not the patients' gender and the examination season, according to multivariate regression analysis. Conclusion. The study has shown low level of vitamin D provision in children with CEB, whilst 25(OH)D concentration depended on the type of disease and the age of patients.